Coworker support as moderator on the relationship between HRM practices and organizational commitment: A proposed framework - Ahmad, Ashfaq; Abdul Majid, Abdul Halim; Mohd Zin, Md. Lazim (2016)
Several factors have been proposed to have influence over organizational commitment; among some of those prominent factors are human resource management practices.However, among the prominent studies on the said relationship; the reported findings are inconsistent.Therefore, it is proposed to incorporate a moderating variable to further explain this relationship.The current study proposed coworker support as moderator on the relationship between HRM practices and organizational commitment.